2016
DOI: 10.1515/bjmg-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and association of 1691 (G>A) FVL, 20210 (G>A) PT and 677 (C>T) MTHFR with deep vein thrombosis in the population of Bosnia and Herzegovina

Abstract: The 1691 (G>A) factor V Leiden (FVL) and 20210 (G>A) prothrombin (PT) mutations are the two most common genetic risk factors in venous thromboembolism. The 677 (C>T) methylene tetrahydrofolate reductase (MTHFR) mutation is the most frequently mentioned as an independent genetic risk factor for venous thromboembolism. As there are limited published data on the prevalence of the 1691, 20210 and 677 mutations in our population, the aim of this study was to determine the frequencies and association of these deep v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
3
6
1
3
Order By: Relevance
“…New reports determined the frequency of factor V Leiden mutation in the European population as about 5% and about 20% in patients with venous thrombosis [16]. While the prevalence of heterozygous prothrombin G20210A genotype among Saudi patients with DVT was 3 (5%) in agreement with those who suggested an insignificant association between prothrombin G20210A and DVT [17]. Heterozygous MTHFR C677T genotype among Saudi female patients with DVT was 6 (10%) and did not reach the significance level (P = 0.558), in agreement with a previous report stating that there is no association between MTHFR C677T and DVT [18].…”
Section: Resultssupporting
confidence: 73%
“…New reports determined the frequency of factor V Leiden mutation in the European population as about 5% and about 20% in patients with venous thrombosis [16]. While the prevalence of heterozygous prothrombin G20210A genotype among Saudi patients with DVT was 3 (5%) in agreement with those who suggested an insignificant association between prothrombin G20210A and DVT [17]. Heterozygous MTHFR C677T genotype among Saudi female patients with DVT was 6 (10%) and did not reach the significance level (P = 0.558), in agreement with a previous report stating that there is no association between MTHFR C677T and DVT [18].…”
Section: Resultssupporting
confidence: 73%
“…Our results similarly correlate with the result of Serbia (11.6% patients VTE) 13 . Other studies from our region report different results in which heterozygotes for FII 20210 were presented in patients with VTE with lower frequency (Croatia 4% and Bosnia and Herzegovina 2.7%) 30,34 .…”
Section: Discussioncontrasting
confidence: 53%
“…The occurrence of the thromboembolic disease is in the line with the simultaneous presence of a gene polymorphisms and environmental risk factors which can partly explain the inconsistent results of similar studies conducted in different geographic regions 10,11,34 . The results of our study show that the presence of polymorphisms FII G20210A and FV G1691A is significantly higher in the VTE group compared to a healthy control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comprehensive study, homozygous MTHFR 677TT genotype was found in 10% of patients with DVT and in 11% of healthy subjects, and the heterozygous MTHFR C677T genotype was found to be similar in both patients with DVT and control group as 43% [31]. In healthy Bosnian population, the prevalence of homozygous and heterozygous MTHFR 677 polymorphisms has been reported to vary between 9%-12%, and 30%-50%, respectively [32]. The prevalence of homozygote for MTHFR 677TT genotype and double heterozygote for MTHFR C677T/ MTHFR A1298C genotypes was found 8.8% and 14.4%, respectively in our previous study in healthy Turkish subjects [25]; similar to the rates of this study 7.4% and 16.29%, respectively.…”
Section: Discussionmentioning
confidence: 98%